ANALISIS PSIKOMETRI INSTRUMEN OPTIMISME PADA MAHASISWA PENULIS SKRIPSI - Laurentius Purbo Christianto (Program Studi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2018)
ABSTRACT The optimism of students in working on the thesis is important to know so that the faculty can make the right policy to ensure students who do the thesis immediately finish it. Related to this, this study tries to develop an optimism scale, which aims to measure optimism in students who work on thesis, in completing their thesis. This scale is a self-report inventory in a Likert scale format. The scale measures the level of respondents' approval of the items that support the construct of optimism. The greater the scale score, the greater the respondents' optimism, while the smaller the scale score, the respondents can be indicated to be less optimistic. Based on the item analysis the scale netted 11 items of scale which had good homogeneity and item discrimination scores. Furthermore, based on the validity test and reliability test, it is known that this scale is valid and reliable. Keyword: optimism, optimism scale